Topology searching algorithm for multi-port hybrid circuit breakers based on graph theory - He, Songming; Zhu, Jin; Zeng, Qingpeng; Guo, Xinming; Yin, Jingyuan; Wei, Tongzhen (Frontiers in Energy Research, 2023)
Due to the significant advantages of low cost, integrated multi-port hybrid DC circuit breakers (M-HCBs) with a reduced number of devices have attracted extensive attention for fault blocking in multi-terminal VSC-HVDC system. However, the current topology exploration by researchers is random, uncertain, and time-consuming. In order to provide more new cost-effective topologies, this paper innovatively proposes a topology searching algorithm for the IGBT-type M-HCB and uses the concept of ‘roadblock’ to simplify the adjacency matrix. It can be used to significantly save time spent on proposing a new M-HCB topology because viable topologies can be quickly and rigorously carried out from a large number of directed graphs using computers. Performance characteristics of all derived topologies are simultaneously obtained, and a comparison can be easily conducted to meet the needs of actual application scenarios. A three-port M-HCB example-specific application is given, along with some detailed output topologies that prove the validity and feasibility of the proposed method.